Concordia, aeternitas Imperii i kwestie dynastyczne w menniczym programie ideologicznym okresu pierwszych Sewerów - Balbuza, Katarzyna (Studia Europaea Gnesnensia, 2015)
The paper analyses all early Severan coinage commemorating the ideas of concord (concordia) in the state, in particular the concepts of marital concord (concordia felix), perpetual concord (perpetua concordia) and eternal concord (concordia aeterna ), against the backdrop of the simultaneously propagated idea of aeternitas Imperii as well as the ideology and policy of succession of the ruling house.